(untitled) (Raparin Journal of Humanities (RJH), 2023)
This research is about (the cancellation of documentary Credit in Iraqi Trade law compared to the standards of the International Chamber of Commerce (UCP 600)). It is an analytical and comparative study, it is a scientific attempt that sheds light on how to cancel the documentary credit and its impact and effects in accordance with international standards in the International Chamber of Commerce (UCP 600), and compares it with the Iraqi Trade Law to identify deficiencies in Iraqi law. In order to be able in the near future to complete the legal deficiencies in Iraqi law and to comply with international standards. Documentary credit is an important method in the field of international trade that makes commercial movement fast between countries and eliminates fear and anxiety among merchants and those doing business because fear and anxiety ultimately slow down commercial activity. Undoubtedly, the law must take its course to regulate these activities in the best manner. Also, in the end, this research presents a set of results and suggestions, such as the solution to readers and researchers, which must be taken into account upon amending the Iraqi Trade law in the future.